Impact of Dose, Sex, and Strain on Oxaliplatin-Induced Peripheral Neuropathy in Mice - Warncke, Urszula O.; Toma, Wisam; Meade, Julie A.; Park, Abigail J.; Thompson, Danielle C.; Caillaud, Martial; Bigbee, John W.; Bryant, Camron D.; Damaj, M. Imad (Frontiers in Pain Research, 2021)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common, dose limiting, and long-lasting side effect of chemotherapy treatment. Unfortunately, no treatment has proven efficacious for this side effect. Rodent models play a crucial role in the discovery of new mechanisms underlying the initiation, progression, and recovery of CIPN and the potential discovery of new therapeutics. However, there is limited consistency in the dose, the sex, age, and genetic background of the animal used in these studies and the outcome measures used in evaluation of CIPN rely primarily on noxious and reflexive measures. The main objective of this study was to provide a comprehensive and systematic characterization of oxaliplatin-induced peripheral neuropathy in mice by using a battery of behavioral, sensory, electrophysiological, and morphometric measures in both sexes of the two widely used strains of mice, C57BL/6J and BALB/cJ. Mice received intraperitoneal injections of 3 mg/kg or 30 mg/kg cumulative doses of oxaliplatin over the course of two weeks. Both doses induced long-term and time-dependent mechanical and cold hypersensitivity. Our results show that 30 mg/kg oxaliplatin reduced the locomotor activity in C57BL/6J mice, and C57BL/6J females showed anxiety-like behavior one-week post completion of treatment. In the same dose group, BALB/cJ males and females sustained a larger decrease in sucrose preference than either male or female C57BL/6J mice. Both strains failed to show significant changes in burrowing and nesting behaviors. Two clinically relevant assessments of changes to the peripheral nerve fibers, nerve conduction and intraepidermal nerve fiber density (IENFD) were evaluated. Only BALB/cJ females showed significant reduction in the nerve conduction amplitude one week after 30 mg/kg oxaliplatin regimen. Moreover, this dose of the chemo agent reduced the IENF density in both sexes and strains. Our findings suggest that mouse strain, sex, and assay type should be carefully considered when assessing the effects of oxaliplatin and potential therapeutic interventions.